A descriptive study to understand how severity of symptoms after completion of treatment impact on the life of oral cancer patients - Goswami, Sourav; Gupta, Subodh Saran (International Journal Of Community Medicine And Public Health, 2019)
Background: Oral cancer is a commonly occurring cancer among Indians, who are mostly habituated to chewing tobacco. It accounts for around 30–40% of all malignant tumors in India and has one of the lowest five years survival rates, as most of them are diagnosed in advanced stages. More so, after the treatment is completed, the patients’ still suffers from a number of symptoms, which are often not taken seriously. The objective of this study was to evaluate the impact of severity of symptomatology of oral cancer after completion of cancer treatment. Methods: EORTC (European organization for research and treatment of cancer) H and N 35 questionnaire (Marathi version) was used to assess the severity of clinical symptoms. 100 consecutive patients of oral cancer who had completed their treatment and came for follow up after 1 to 3 months of treatment completion were enrolled for the study after taking informed written consent. The study was initiated after obtaining ethical approval from the institutional ethics committee. Statistical analysis was done using R software. Results: Age of the patient, status of insurance, time gap between symptom onset and diagnosis, socio-economic status and stage of oral cancer were included in the final model of multivariate analysis. Time gap between symptom onset and diagnosis (in months) was also found to be associated significantly to head and neck symptoms. Participants from higher socio-economic status were found to have fewer head and neck symptoms and this association was found statistically significant. Conclusions: Assessment of severity of symptomatology should be routinely practiced among patients who had completed their treatment and come for follow up. This needs to be followed by guidance and individualized interventions for improving the quality of life of the treated patients.